“The New Men”: The Rahima’s Experiences in the Gender Sensitivity Construction among Marriage Registrar in Lampung Indonesia (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Efforts to prevent gender-based violence will progress slowly without involving men. Socialization and education tend to be targeted towards women’s groups, with few including men as subjects in the anti-violence education process. This article discusses several important lessons learned from the mentoring process of Marriage Registrar Officials at the Office of Religious Affairs in East Lampung, Indonesia, by the Rahima Association. The study is the result of observations on the mentoring process of Marriage Registrar Officials who have internalized the values of justice and reciprocity in family relations. The research data are supported by interviews, focus group discussions, and documentation. This article argues that the involvement of male religious figures in preventing family violence is essential for two reasons. First, in textual societies, male ulama have a strategic role in reproducing more egalitarian and just knowledge. Second, the process of building gender-just awareness requires authoritative actors in the process of building knowledge from shared experience to be more legitimate. The article also explains the theoretical foundations of the successful mentoring approach that has transformed the outlook of male Marriage Registrar Officials who have the drive to effect change in Muslim society regarding equal and just family relations through their duties and functions.
Keywords: New Men; Gender Sensitivity; Marriage Registrar Officials; Masculinity; Gender-Based Violence